2019
DOI: 10.1021/acs.est.9b05489
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Murine Norovirus and Fecal Coliforms by Ferrate(VI) in Secondary Effluent Wastewater

Abstract: Ferrate­(VI) (FeVIO4 2, Fe­(VI)) is an emerging oxidant/disinfectant to treat a wide range of contaminants and microbial pollutants in wastewater. This study describes the inactivation of murine norovirus (MNV) by Fe­(VI) in phosphate buffer (PB) and secondary effluent wastewater (SEW). The decay of Fe­(VI) had second-order kinetics in PB while Fe­(VI) underwent an initial demand followed by first-order decay kinetics in SEW. The Chick–Watson inactivation kinetic model, based on integral CT (ICT) dose, well fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 94 publications
0
33
0
1
Order By: Relevance
“…Coronavirus-type viruses may inactivate in wastewater, with temperature highly influencing the inactivation rate (Wigginton and Boehm 2020). During wastewater treatment, oxidants and disinfectants can inactivate enveloped viruses (Manoli et al 2020). However, many poor communities lack the infrastructure to provide clean water, and therefore would face exposure of infectious viruses.…”
mentioning
confidence: 99%
“…Coronavirus-type viruses may inactivate in wastewater, with temperature highly influencing the inactivation rate (Wigginton and Boehm 2020). During wastewater treatment, oxidants and disinfectants can inactivate enveloped viruses (Manoli et al 2020). However, many poor communities lack the infrastructure to provide clean water, and therefore would face exposure of infectious viruses.…”
mentioning
confidence: 99%
“…No âmbito da remoção de cargas virais, Manoli et al (2019) demonstra a capacidade do ferrato (VI), como desinfetante, à desativação de vírus, indicando os danos à proteína dos capsídeos e ao genoma como possíveis causadores da desativação dos patógenos.…”
Section: C) Ferrato (Vi)unclassified
“…Fe(VI) is an environmental benign disinfectant with the ability of damaging the genome and the oxidant-sensitive protein structures of microorganisms, hindering their growth and reproduction (Hu et al, 2012;Yan et al, 2020). Previous studies have demonstrated that Fe(VI) can effectively inactivate a wide variety of microorganisms including cyanobacteria (Sharma, 2007), bacteriophage MS2 (Hu et al, 2012), f2 virus (Schink and Waite, 1980), norovirus (Manoli et al, 2020), Bacillus cereus, Escherichia coli, Staphylococcus aureus (Sharma, 2007), micro-algae (Fan et al, 2018), and so on. It was reported that a Fe (VI) CT dose of about 3.5 (mg$min)/L was required for the 2 log removal of Escherichia coli at pH 7.0, and at a Fe(VI) CT dose of 2.0 (mg$min)/L at pH 7.0, a 2 log removal of MS2 can be obtained (Hu et al, 2012;Manoli et al, 2020).…”
Section: Inactivation Of Microorganismsmentioning
confidence: 99%
“…Previous studies have demonstrated that Fe(VI) can effectively inactivate a wide variety of microorganisms including cyanobacteria (Sharma, 2007), bacteriophage MS2 (Hu et al, 2012), f2 virus (Schink and Waite, 1980), norovirus (Manoli et al, 2020), Bacillus cereus, Escherichia coli, Staphylococcus aureus (Sharma, 2007), micro-algae (Fan et al, 2018), and so on. It was reported that a Fe (VI) CT dose of about 3.5 (mg$min)/L was required for the 2 log removal of Escherichia coli at pH 7.0, and at a Fe(VI) CT dose of 2.0 (mg$min)/L at pH 7.0, a 2 log removal of MS2 can be obtained (Hu et al, 2012;Manoli et al, 2020). Although the disinfection performance of the conventional disinfectants closely associates with pH in addition to the type of microorganisms, the influence of pH on the disinfection performance of Fe(VI) is less than that of other conventional disinfectants, which further demonstrates the superiority of Fe(VI) technologies.…”
Section: Inactivation Of Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation